A potential treatment for erectile dysfunction: Effect of platelet-rich plasma administration on axon and collagen regeneration in cavernous nerve injury - Ismy, Jufriady; Khalilullah, Said A.; Maulana, Reza; Hidayatullah, Furqan (Narra Sains Indonesia, 2024)
Recent studies highlighted the role of platelet-rich plasma (PRP) in progenitor cell homing, migration, and nerve cell regeneration while also inhibiting fibrosis and apoptosis in cavernous nerve injury (CNI). The aim of this study was to investigate the effect of PRP administration on axon and collagen regeneration in CNI. A true experimental study using a post-test-only control group design was conducted. Twenty-five male Wistar rats (Rattus norvegicus), weighing 200–300 grams, were divided into five groups: two control groups (sham procedure and negative control), and three experimental groups receiving local PRP, intraperitoneal PRP, and a combination of local and intraperitoneal PRP. The cavernous nerve was injured with a hemostasis clamp for one minute before 200 µL of 200 PRP was injected locally, intraperitoneally, or both, depending on the group. After four weeks, the rats were euthanized, tissue segments (2 mm) from each cavernous nerve and mid-penis were collected and analyzed for collagen density, axon diameter, and number of myelinated axons. Our study found that collagen growth was slower in CNI group without PRP (sham procedure) compared to all PRP groups (local, intraperitoneal, and combination). The intraperitoneal PRP group had the highest collagen density at 5.62 µm; however, no significant difference was observed in collagen density among all groups (p=0.056). Similar axon diameter was found across the groups, with no statistically significant difference observed (p=0.856). In the number of myelinated axons, a significant difference was found among all groups with significantly more axons in local PRP and combined local and intraperitoneal PRP groups compared to others (p=0.026). In conclusion, PRP administration improved a number of myelinated axons in CNI, suggesting PRP role in CNI regeneration and the potential for an innovative approach to treating erectile dysfunction associated with CNI.